Potential Usage of Solar Energy as a Renewable Energy Source in Petukangan Utara, South Jakarta - Eka Purwa Laksana; Yani Prabowo; Sujono Sujono; Rummi Sirait; Nifty Fath; Ardyono Priyadi; Mauridhi Hery Purnomo (Universitas Syiah Kuala, 2021)
Indonesia is a tropical country located on the equator. The average intensity of solar radiation in Indonesia is 4.8 kWh/m2. This makes Indonesia a country with new and ren ewable energy potential, one of which is solar panel technology. The first step that must be done in the process of installing solar panels in a place is to analyze the potential of solar energy. In this study, an analysis of the potential of solar energy as a new renewable energy source has been carried out at Budi Luhur University, North Petukangan, South Jakarta. Based on the research results, the maximum photovoltaic efficiency that can be achieved is 21.45%. During the day, the efficiency of the solar panels increases along with the ncrease in the value of the voltage obtained. However, the higher the panel temperature, the lower the efficiency of the solar panel. Therefore, a cooling system is needed to anticipate this.